Branding Luwu Coffee as a Signature Souvenir from Luwu Regency, South Sulawesi - Noerhatini, Pathmi; Kurniasih, Nia; Roza, Prima; Fauzi, Ridwan (The Eastasouth Management and Business, 2025)
This article aims to analyze the branding strategy of Arabica coffee from Luwu Regency as a signature souvenir that is expected to enhance local economic value. The research employs a quantitative approach through coffee quality testing and a qualitative approach using a case study method, involving interviews with farmers, business actors, and relevant stakeholders. Data were also obtained through direct observation and analysis of supporting literature. The study was conducted in Latimojong District, specifically in Boneposi and Tolajuk Villages, as well as in Belopa City, Luwu Regency, South Sulawesi. The research was carried out in August 2023 and July 2024. The findings reveal that the unique flavor of Luwu Arabica coffee, supported by ideal geographical conditions and local cultural narratives, holds significant potential to be positioned as a premium product. Effective branding strategies include narratives linked to local culture, digital-based promotional designs, and integration with the tourism sector. The implications of branding Luwu Arabica coffee include increased farmers' income, job creation, and the strengthening of the region's identity as a producer of high-quality coffee. This article also highlights the importance of collaboration between the government, business actors, and local communities to ensure the success of this branding effort in supporting the economic well-being of Luwu society while introducing Indonesia’s unique products to a broader audience.